2021
DOI: 10.1038/s41467-021-22967-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting human Acyl-CoA:cholesterol acyltransferase as a dual viral and T cell metabolic checkpoint

Abstract: Determining divergent metabolic requirements of T cells, and the viruses and tumours they fail to combat, could provide new therapeutic checkpoints. Inhibition of acyl-CoA:cholesterol acyltransferase (ACAT) has direct anti-carcinogenic activity. Here, we show that ACAT inhibition has antiviral activity against hepatitis B (HBV), as well as boosting protective anti-HBV and anti-hepatocellular carcinoma (HCC) T cells. ACAT inhibition reduces CD8+ T cell neutral lipid droplets and promotes lipid microdomains, enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 70 publications
5
55
0
Order By: Relevance
“…In line with this, in chronic hepatitis B inhibition of cholesterol esterification by the acyl-CoA:cholesterol acyltransferase (ACAT), that catalyzes the esterification of excess intracellular cholesterol for storage in lipid droplets, enhanced TCR signaling upon CD8 T cell stimulation, by reducing lipid droplet formation and diverting cholesterol to the cell membrane [69] (Figure 2, Tables 1 and 2). This strategy has been shown to be active both to enhance HBV-and HCC-specific T cell proliferation and effector functions, by optimizing cells bioenergetics, and to exert an antiviral effect by reducing HBV virions and viral particles formation in vitro [69].…”
Section: Established Chronic Infectionsmentioning
confidence: 66%
See 1 more Smart Citation
“…In line with this, in chronic hepatitis B inhibition of cholesterol esterification by the acyl-CoA:cholesterol acyltransferase (ACAT), that catalyzes the esterification of excess intracellular cholesterol for storage in lipid droplets, enhanced TCR signaling upon CD8 T cell stimulation, by reducing lipid droplet formation and diverting cholesterol to the cell membrane [69] (Figure 2, Tables 1 and 2). This strategy has been shown to be active both to enhance HBV-and HCC-specific T cell proliferation and effector functions, by optimizing cells bioenergetics, and to exert an antiviral effect by reducing HBV virions and viral particles formation in vitro [69].…”
Section: Established Chronic Infectionsmentioning
confidence: 66%
“…In addition, the evidence that sustained responses upon PD-1 blockade treatment are detectable only in a limited proportion of HCC and chronic hepatitis B patients suggests the need of developing predictive parameters of response to treatment in order to select the patient cohorts that can benefit of check-point inhibition and to design further modulatory approaches to combine with PD-1 blockade to be used in alternative to it. Along with this line of possible strategies, inhibition of acyl-CoA:cholesterol acyltransferase (ACAT) has recently been reported to significantly improve in vitro HBV-specific CD8 T cell responsiveness to PD-1 blockade pointing to the possibility to combine metabolic and immune checkpoint modulation for the functional cure of HBV infection and HBV-related HCC [69].…”
Section: Boosting Adaptive Immune Response By Blocking Co-inhibitory Pathwaysmentioning
confidence: 99%
“…In support, we showed that both serum and isolated VLDL and LDL from JSLE patients with active disease increased the level of lipid rafts in T-cells and B-cells associated with increased immune activation. Importantly, immune cell lipids are now recognised as targets for immunotherapies in cancer; inhibition of acetyl-CoA acetyltransferase 1 (ACAT1, cholesterol esterification enzyme that increases immune cell cholesterol levels) improves the efficacy of anti-PD1 therapy in melanoma and antiviral activity against hepatitis B due to a specific increase in CD8+ T-cell effector function against melanoma growth through lipid raft associated T-cell receptor (TCR) clustering and signalling [28,47]. Resistance to therapy in patients with ER + breast cancer is also associated with upregulated cholesterol biosynthesis enzymes which is reversed experimentally by targeting lipid biosynthesis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in clinically active disease, circulating atheroprotective HDL subsets had a negative correlation, and atherogenic lipoprotein subsets (LDL/VLDL) had a positive correlation, with circulating lipids typically enriched in lipid raft microdomains (sphingomyelin, cholesterol, phosphoglycerides, phosphatidylcholine, and other cholines, Figures 3F and 4A); conversely, these correlations were reversed or decreased respectively in patients with clinically inactive disease. CD4+ T-cell, CD8+ T-cell, and B-cell lipid raft expression (assessed using the surrogate lipid raft marker cholera-toxin B [16,28]) were increased in patients with clinically +/− serologically active disease (Supplementary Figure S3) and correlated positively with disease activity measures including SLEDAI, erythrocyte sedimentation rate (ESR) and anti-double stranded DNA antibodies (dsDNA) and negatively with complement C3 (Figure 4B). Furthermore, atherogenic lipoproteins (ApoB, ApoB:A1 ratio, VLDL, IDL, and LDL) correlated positively, and atheroprotective lipoproteins (ApoA1 and HDL) correlated negatively, with lipid rafts in T-cells and B-cells (Figure 4C, Table S6), suggesting a role of lipoproteins in altering lymphocyte lipid metabolism and function.…”
Section: Lipid Raft Signalling Platforms Correlate With Lipoprotein Expression In Active Jsle Patientsmentioning
confidence: 99%
“…Reduced cholesterol esterification in CD8 + T cells increased plasma membrane cholesterol levels and subsequent lipid raft–associated T cell receptor clustering and signaling, thereby increasing T cell cytotoxicity against melanoma growth. ACAT inhibition can also boost the antiviral activity of CD8 + T cells against hepatitis B by promoting lipid raft signaling in vitro ( 159 ).…”
Section: Biologicsmentioning
confidence: 99%